2020
DOI: 10.3390/ijms21197182
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Lysine Acetylation Contributes to the Pathogenesis of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is one of the most common neurodegenerative disorders. The neuropathological features of PD are selective and progressive loss of dopaminergic neurons in the substantia nigra pars compacta, deficiencies in striatal dopamine levels, and the presence of intracellular Lewy bodies. Interactions among aging and genetic and environmental factors are considered to underlie the common etiology of PD, which involves multiple changes in cellular processes. Recent studies suggest that changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 132 publications
(170 reference statements)
0
27
0
Order By: Relevance
“…Parkinson’s disease (PD), the most common neurodegenerative movement disorder, affects approximately 1% of the population over 60 years old, and its incidence dramatically increases to approximately 5% in the population greater than 85 years of age ( Li and Le, 2020 ; Wang et al, 2020b ). PD is a chronic, irreversible, and complex neurodegenerative disease with several typical motor impairments including resting tremor, bradykinesia, rigidity, and postural imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD), the most common neurodegenerative movement disorder, affects approximately 1% of the population over 60 years old, and its incidence dramatically increases to approximately 5% in the population greater than 85 years of age ( Li and Le, 2020 ; Wang et al, 2020b ). PD is a chronic, irreversible, and complex neurodegenerative disease with several typical motor impairments including resting tremor, bradykinesia, rigidity, and postural imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that the number of tandem repeats and methylation levels of the first intron of SLC6A3 gene might be related to nicotine dependence and a potentially increased tendency to start smoking and an impaired ability to quit [ 55 ]. Another recent study demonstrated that the DNA methylation rates of DRD2 in peripheral leukocytes were reduced in PD patients [ 102 ]. DRD2 is considered a risk factor for PD, and ANKK1/DRD2 genetic region variants have been associated with nicotine dependence in males in a Chinese study [ 56 ].…”
Section: Environmental Impact On Epigenetic Modifications In Pdmentioning
confidence: 99%
“…Although the exact mechanism remains unknown, polo-like kinases (PLK) could be responsible for regulating this phosphorylation event in the serine 129 [143]. Apart from phosphorylation, lysine acetylation status of α-synuclein has been involved in the pathogenesis of the disease as well [144]. In addition, this protein modification impairs mitophagy in fibroblasts, as shown for PD patients [145].…”
Section: Dietary Polyphenols and Neurodegenerationmentioning
confidence: 99%